Making explicit agricultural ecosystem service trade-offs: a case study of an English lowland arable farm. Issue 3 (2nd July 2016) - Field, Rob H.; Hill, Rachel K.; Carroll, Matthew J.; Morris, Antony J.
Abstract : European farmland hosts a species assemblage of animals and plants which have undergone declines through the late twentieth and early twenty-first centuries, at least partly as a result of increased productivity. Further increases in human populations, changes in availability and cost of raw materials, policy constraints, price volatility and climatic changes will further drive greater efficiency and high yields in agriculture, with the risk of further adverse environmental impacts. We assess the effects of different management priorities (production-driven cropping vs. wildlife-friendly farming) at an arable farm in eastern England on food production, greenhouse gas (GHG) emissions and biodiversity. We modelled one actual and three alternative cropping scenarios using actual yields from the farm over 13 years, to calculate total yields and those foregone for agri-environmental measures. We measured crop yields, relative abundance of 19 farmland bird species, and CO2 and N2 O emissions related to crop production. Removing up to 10.5% of land from production coupled with a more diverse rotation (including legumes) resulted in a large increase in breeding birds (177%) and reduction of 9.4% in GHG emissions at the cost of 9.6% of food energy. Food protein lost was only 2.9%. A smaller increase in bird numbers of 50% could be achieved at a much smaller cost to yield (∼1.7% energy or protein) but with correspondingly smaller emissions reductions (1.2%). Results are discussed within the context of continued biodiversity loss to agriculture, increasing food demand and changing diets.